Development of an Instructional Guidebook In the Multimedia Laboratory - Ikanubun, Lucia Ekawati; Dewi, Laksmi; Mulyadi, Dadi (Cattleya Darmaya Fortuna, 2025)
Multimedia laboratory is crucial for supporting students' learning process in educational technology program. This relates to the implementation of knowledge into skills in producing digital learning media. However, many students still find it challenging to understand the function and use of tools and equipment in producing digital learning media due to the absence of a handbook to support learning in the lab. This situation came to light during the writer's observation of issues during the implementation of the Actualization phase of the 2024 CPNS basic training. This study aims to develop an instructional guidebook for students in the educational technology program at Universitas Pendidikan Indonesia (UPI). This study employed D&D with 4D Model: Define, Design, Develop, and Disseminate. The learning guidebook is produced in an E-book format, linked to 12 tutorial videos, that activates students to be more familiar with the lab equipment, know how to use the lab hardware and software and produce digital learning media. This research provides contribution to increase students' practical skills and foster the effectiveness of learning practice in the multimedia lab.